Pengembangan E-Modul pada Materi “Melakukan Instalasi Sistem Operasi Jaringan Berbasis GUI dan Text” untuk Siswa Kelas X Teknik Komputer dan Jaringan SMK Negeri 3 Singaraja - I Nyoman Sudiartayasa Adiputra; Nyoman Sugihartini; Dessy Seri Wahyuni; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
This study aimed (1) To design and implement the development of the E-Module on Matter ‘Melakukan Instalasi Sistem Operasi Jaringan Berbasis GUI dan Text’ for class X Studen’ts Skills Program in Computer Engineering and Networks SMK Negeri 3 Singaraja. (2) To describe the response of Class X students Skills Program in Computer Engineering and Networks SMK 3 Singaraja on the Development of E-Module on Matter ‘Melakukan Instalasi Sistem Operasi Jaringan Berbasis GUI dan Text’. Research method that is used in this study is Research and Development (R & D ) with applied the method ADDIE model. The subjects are students of class X TKJ-1 SMK N 3 Singaraja school year 2013/2014. To find out the students' response to emodules obtained using the questionnaire method. The results of the analysis of the student response data showed that the percentage of students who responded very positively by 66.67% the percentage of students who responded positively by 33.33%, and no students responded less positively, not negative or very negative. Based on the results of the analysis of total percentage of student’s response to the development of e-module on matter